Impact of asset quality on bank profitability - Case Study - Kasavica, Petar; Jović, Zoran (Industrija, 2015)
The paper explores the impact of asset quality on banks' profitability in the case of a commercial bank in Serbia. Parameters covered as key indicators of the impact on profitability are: maturity of the portfolio, clients’ ratings, NPL (Non-Performing) loans, effective coverage of the total portfolio with collaterals and effective coverage of NPL portfolio with collaterals. To test the influence of parameters on the dependent variables, we used the fixed effect regression model. The success of the model is monitored through Schwarz's Bayesian Criterion where the absolute number shows the success of the model - the lower the number, the better the model. The research results indicate the manner and intensity of the impact of the discussed parameters on the margins of profitability. Applied research model is also useful in analyzing the impact of asset quality on the profitability of other commercial banks. The scientific contribution of the research lies in the fact that it offers a new way of testing theoretical assumptions that emerged from adapting practical methods to the needs for making general conclusions and theoretical generalizations, based on which we create space for further scientific research and improvements in this area.
Keywords: contribution margin; NPL; Profitability of banks; Asset quality